Preparation of macroporous poly(N-isopropylacrylamide) hydrogels using a suspension–gelation method. (May 2015) - Sato, Ryuichi; Noma, Ryoko; Tokuyama, Hideaki
Graphical abstract: Highlights: Composite and macroporous hydrogels were prepared using a suspension–gelation method. Microcapsules of calcium alginate were used as a pore template. Thermosensitive N -isopropylacrylamide hydrogels was used as a continuous phase. Thermosensitive swelling properties and mechanical properties were characterized. Abstract: A macroporous hydrogel, consisting of a homogeneous cross-linked polymer network and linear polymers containing randomly distributed sphere-like cavities, was developed using a suspension–gelation method. This method involves the synthesis of composite hydrogels containing distributed microcapsules as a pore template (porogen) by free radical polymerization, followed by a chemical treatment to break down the structure of the microcapsules within the hydrogels. Macroporous hydrogels were successfully synthesized in a model system consisting of thermosensitive N -isopropylacrylamide hydrogels and physically cross-linked microcapsules of calcium alginate, which were prepared using an electrostatic atomization method. Observation of the internal structure of the hydrogels using scanning electron microscopy revealed that the composite hydrogels contain microcapsules and the macroporous hydrogels have non-interconnected macropores created by the microcapsules as the template. The thermosensitive swelling properties and the mechanical properties of the hydrogels were characterized.